Perfil farmacocinético do metamizol isolado e associado ao tramadol após administração intravenosa em asininos - Macêdo, Luã Barbalho de (Universidade Federal Rural do Semi-Árido, 2021)
The empirical extrapolation of the therapeutic protocols indicated for animals, although a routine practice, does not take into account the particularities of each species, increasing the risks of low efficacy in treatments, either by underdoses or by overdoses. The objective was to evaluate the pharmacokinetic profile of metamizole administered intravenously in isolation and in association with tramadol in donkeys. The ten animals were included in all study groups, with a 15-day rest period between treatments. The animals received four treatments. In the treatment M10 metamizole at a dose of 10 mg/kg, M25 - metamizole 25mg/kg and M10T2 - 10 mg/kg of metamizole combined with 2mg/kg of tramadol and in M25T2, 25 mg/kg metamizole with 2mg/kg tramadol. All treatments were performed in a single dose and intravenously. After predetermined times, blood samples were collected for further analysis. Plasma aliquots were processed and injected into the ultra-performance chromatographic system coupled to a mass spectrometer (UPLC-MS / MS). During the collections, the animals were observed for possible adverse manifestations. The parameters evaluated were: the maximum plasma concentration (Cmax), the time to reach the Cmax (Tmax), the area under the plasma concentration curve from time zero until the moment of the last measurable concentration (AUC0 → t) and the extrapolation of the AUC to infinity (AUC0 → ∞), apparent volume of distribution (Vz/F), apparent clearance (Cl/ F), elimination constant (Ke); elimination half-life (t1 / 2); Mean residual time until the last measurement (MRT0 → t), Mean residual time from zero to infinity (MRT0 → ∞), for drugs and their main metabolites. In groups M10 and M25, the parameters AUC0 → t, AUC0 → ∞, Cmax showed a significant increase in the two metabolites of metamizole in animals in the group M25. While Tmax, Vz / F and Cl / F had no statistical difference between groups. After intravenous administration of treatments M10T2 and M25T2, TRA, MAA, AA were detected within 24 hours of analysis and M1 up to 12 hours. Analyzing the TRA metabolite, it was observed that AUC0 → ∞ and CL / F were higher in the group treated with 10mg/kg of metamizole when compared to the 25mg/kg group. While the t ½; MRT0 → ∞; MRT0 → t are significantly higher in the M25T2 group. Regarding its by-product, M1, t 1/2; MRT0 → ∞; MRT0 → t were significantly higher in the second group. The Vz / F; MRT 0 → ∞, t1/2 of MAA and MRT0 → t of AA varied significantly between groups, being higher in animals that received 25mg/kg of Metamizole. Based on the results, it is possible to state that it was successful since it was possible to develop an analytical method capable of detecting and quantifying both drugs and their main metabolites in donkey blood for up to 48 hours. In addition, it proved that there are changes in some pharmacokinetic parameters when different doses of metamizole are administered and that they interfere with the metabolism of metamizole itself as well as tramadol and its most active metabolite, O-desmethyltramadol and that these findings may support future clinical trials for analgesic efficacy or even establish an appropriate dosage for donkeys
Keywords: Analgésicos; Equídeos; Metabólitos; Dipirona; Farmacocinética; Analgesics; Equidae; Metabolites; Dipyrone; Pharmacokinetics; CIENCIAS AGRARIAS::MEDICINA VETERINARIA